The Making of a Classification Scheme for Libraries of Judaica - Elazar, David (Judaica Librarianship, 2008)
This paper describes the history of A Classification System for Libraries of Judaica, its development, the process involved in preparing the second and third revisions, and its use in various libraries.The authors of the scheme contend that there was-and is-a need for a classification system for libraries of Judaica to classify and arrange their collections according to Jewish concepts based upon Jewish thought and terminology.